Dukungan Sistem Kepercayaan Dalam Kejahatan - A. Josias Simon Runturambi (Antropologi Indonesia, 2003)
Crime with a spiritual nuance is a real phenomenon in Indonesia Society. The supernatural association which is characteristic of this crime has made it a type of crime with a high dark number. The disclosure of locally situated, mystic cases is often limited to the criminal act alone, and there is rarely any intensive investigation into the social cultural processes that underlie the act. This article presents a discussion on the belief systems that play a part in the social cultural processes that result in criminal acts. The author also explains the difficulties in preventing this type of crime, as it relates to social cultural problems and the ineffectiveness of law enforcement.